Dispersive detection of radio-frequency-dressed states - Jammi, Sindhu; Pyragius, Tadas; Bason, Mark G.; Marin Florez, Hans; Fernholz, Thomas (American Physical Society, 2018)
We introduce a method to dispersively detect alkali atoms in radio-frequency dressed states. In particular, we use dressed detection to measure populations and population differences of atoms prepared in their clock states. Linear birefringence of the atomic medium enables atom number detection via polarization homodyning, a form of common path interferometry. In order to achieve low technical noise levels, we perform optical sideband detection after adiabatic transformation of bare states into dressed states. The balanced homodyne signal then oscillates independently of field fluctuations at twice the dressing frequency, thus allowing for robust, phase-locked detection that circumvents low-frequency noise. Using probe pulses of two optical frequencies, we can detect both clock states simultaneously and obtain population difference as well as the total atom number. The scheme also allows for difference measurements by direct subtraction of the homodyne signals at the balanced detector, which should technically enable quantum noise limited measurements with prospects for the preparation of spin squeezed states. The method extends to other Zeeman sublevels and can be employed in a range of atomic clock schemes, atom interferometers, and other experiments using dressed atoms.